Kesesuaian Konsep Livability pada Permukiman disekitar Tempat Pembuangan Akhir - Pratama, Muhammad Ihsya Anugrah; Rahayu, Murtanti Jani; Suminar, Lintang (REKSABUMI, 2025)
Livability is the comfort of residing in an environment (Lynch, 1998) and reflects the quality of life in settlements. Areas around the Putri Cempo Landfill, though violating PUPR Ministerial Regulation No.3/2013 and facing environmental and health issues, remain a livelihood source for low-income migrants. This study analyzes the suitability of the Livability concept based on seven components (economy, health, environment, infrastructure, safety, community participation, and building conditions) using a quantitative descriptive method through field observations, questionnaires (100 respondents), and weighting analysis. Results show a Livability score of 74.42 (moderately suitable), with optimal achievements in safety (97.5), building conditions (96.5), and health (95), but low scores in environmental quality (20.75) due to air pollution and limited community participation (36.5). Most residents rely on the informal sector (62%) with incomes ≥IDR 2.5 million/month (72%), while basic infrastructure is adequate except for GOS (12%). Although 95% of respondents reported no severe health issues, environmental risks persist. The conclusion emphasizes the need for integrated interventions to improve air quality, expand public spaces, and strengthen community participation to achieve sustainable settlements aligned with Livability principles.